The Diversity index and Importance Value of Herbaceous Vegetation in the Joko Tarub Forest Tuban - Yudhistian Yudhistian; Dede Nuraida; Susi Novita Sari; Fitriatus Sholikah (Jurnal Penelitian Pendidikan IPA, 2025)
This study aims to determine the diversity index and the importance value index of herbaceous plants found around the Joko Tarub Forest Tuban. The type of research is quantitative descriptive with a sampling method using the quadrat technique. The quadrates were made with a size of 1 x 1 m as many as 10, as a measurement area. The data collection technique was carried out by recording the names of plants and their numbers found in each quadrat. In addition, the area covered by each plant in the quadrat was also calculated. The data analysis was carried out by calculating the density of species, dominance, and frequency as a basis for calculating the important value index. In addition, the Shannon-Wienner diversity index was also calculated to determine the level of diversity of herbaceous plants living in the area. From the results of this study, 10 types of herbaceous plants were found which are included in 9 Families. Of the 10 types of plants found, those with a high importance value index are Synedrella nodiflora and Crassocephalum crepidioides with values ​​of 53.61 and 44.37 respectively. The herbaceous plant diversity index in the region is in the moderate with a value of 1.89